Bullying? Can the SASADU Program Provide a Lasting Solution in Indonesian Schools? - Hanan Heriyaman; Intan Balqis (WISE Pendidikan Indonesia, 2024)
Bullying remains a pervasive issue in schools, significantly impacting students' mental health and well-being. SMPN 1 Jatinunggal, like many schools, faces challenges in effectively addressing and preventing bullying and cyberbullying. The SASADU program aims to prevent and address bullying in the school environment by increasing awareness, facilitating easy reporting, and ensuring effective intervention. This community service activity employs a digital approach through the SASADU application, integrating educational initiatives, anonymous reporting, and continuous monitoring. Activities include socialization through seminars and posters, simulation of the application usage, ongoing mentoring, and regular evaluation. The SASADU program has significantly enhanced students' understanding of bullying, encouraged anonymous reporting, and improved the effectiveness of the Violence Prevention and Handling Team (TPPK). The program has led to increased awareness, early detection, and proactive handling of bullying incidents, creating a safer and more supportive school environment. The SASADU program contributes to the well-being of the school community by fostering a culture of openness and responsiveness. Despite challenges such as ensuring consistent technology access and maintaining data confidentiality, the program's comprehensive approach offers a sustainable solution for bullying prevention. Future initiatives should focus on expanding technology access, continuous training for staff, strengthening data security protocols, and increasing community involvement. These steps can build on SASADU's success and further enhance the safety and inclusiveness of educational environments.